Kontekstualisasi Cinta dan Kemanusiaan Perspektif Abû Hâmid Al-Ghazâlî - Wasid, Wasid (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This paper is an attempt to refresh the understanding of the concepts of Sufism, particularly the concept of mahabbah of al-GhazÃ¢lÃ®. In the course of time, an understanding of the concepts of Sufism often narrowed and this impressed to the practices of Sufism that only oriented to total devotion to God without any awareness to implement the devotion as a code of ethics in the social life. Through his work, IhyÃ¢â âUlÃ»m al-DÃ®n, al-GhazÃ¢lÃ® reviewed concepts, meaning, causes, nature and connection of mahabbah with humanitarian values. Al-GhazÃ¢lÃ® realized that the peak of happiness and peace of mind is the achievement of a person to the true knowledge, which is maârifat AllÃ¢h. However, to him, the true knowledge arises from someoneâs persistence in affirming its sincerity to God as the implementation of his/her true love that is inimitable. This sincere love gave rise to a worldview that His love is the source of all forms of love to other than Him, the humanbeings and the universe.